Current–Voltage Unbalanced Distribution AC Optimal Power Flow for Advanced Distribution Management System Applications - Zahra Soltani; Mojdeh Khorsand; Shanshan Ma (IEEE Open Journal of Industry Applications, 2024)
Modern distribution systems are changing from passive load serving networks to active load and generation-inclusive networks. Accurate distribution systems modeling is critical for effective distribution system control, operation, and planning. This article proposes novel nonlinear and convex ac optimal power flow (ACOPF) models based on current–voltage (IVACOPF) formulation for an unbalanced distribution system with distributed energy resources (DERs). In the proposed formulation, untransposed distribution lines, shunt elements of distribution lines, distribution transformers, and DERs are modeled. The proposed nonlinear IVACOPF model is linearized and convexified using the Taylor series. The accuracy of the proposed nonlinear and convex IVACOPF approaches for modeling unbalanced distribution systems is compared with OpenDSS and the widely used LinDistFlow method. The proposed accurate convex IVACOPF model has multiple applications for distribution systems management, planning, and operation. Applications of the proposed model on two key parts of advanced distribution management systems (ADMS)—DERs scheduling and state estimation—are presented in this article. The proposed models are tested on the distribution feeder of an electric utility in Arizona with 2100 primary nodes and a large number of rooftop photovoltaic units. The results confirm the accuracy and effectiveness of the proposed IVACOPF for both examined ADMS applications.